Pengaruh Struktur Modal dan Struktur Aset Terhadap Kinerja Keuangan Perusahaan Teknologi yang Terdaftar di Bursa Efek Indonesia - Rahmah, Wahyuni; Budianto, Yan Rezky; Wawo, Andi Basru (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyse the influence of capital structure and asset structure on the financial performance of technology sector companies listed on the Indonesia Stock Exchange during the period 2019–2023. The study employs a quantitative approach with an explanatory design. The study population consists of 22 technology companies, with a sample of 7 companies selected through purposive sampling based on criteria of data completeness and consistency of financial statements. The data used are secondary data sourced from the companies’ annual financial statements. Data analysis was conducted using descriptive statistics and panel data regression to test the influence of variables simultaneously and partially. The results indicate that capital structure and asset structure simultaneously have a positive and significant influence on financial performance. Partially, capital structure, proxied by the Debt to Equity Ratio (DER), has a negative and significant effect on financial performance, whilst asset structure, proxied by the Fixed Asset Ratio (FAR), has a positive but insignificant effect. These findings indicate that the management of capital structure plays a crucial role in determining the financial performance of technology companies.